Seventh Evaluation Report on Community Development and Some Allied Fields - Planning Commission (Planning Commission, 1960)
The present report, the Seventh Evaluation Report is, in more than one sense, a departure from its predecessors. In the first place, it contains studies other than evaluation studies. There are two sets of case studies of successful panchayats and cooperatives and also a fragmentary study of rural unemployment. All these studies throw light on important problems with which the C.D. programme is concerned; but they have not been prepared from the point of view of what contribution the programme may have made to their solution.
Government of India Programme Evaluation Organisation Planning Commission
Government of India Programme Evaluation Organisation Planning Commission